2021
DOI: 10.1101/2021.05.04.442701
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 cell-to-cell infection is resistant to neutralizing antibodies

Abstract: The COVID-19 pandemic caused by SARS-CoV-2 has posed a global threat to human lives and economics. One of the best ways to determine protection against the infection is to quantify the neutralizing activity of serum antibodies. Multiple assays have been developed to validate SARS-CoV-2 neutralization; most of them utilized lentiviral or vesicular stomatitis virus-based particles pseudotyped with the spike (S) protein, making them safe and acceptable to work with in many labs. However, these systems are only ca… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 94 publications
(141 reference statements)
0
2
0
Order By: Relevance
“…It is important to highlight that despite the fact that the pseudotyped SARS-CoV-2 virus has been widely used to study the native virus, it has several limitations worth considering, since it can only mimic the upstream cellular entry and cannot trigger the downstream immune responses within infected cells like the native virus, hence it is not suitable for studies involving immune responses ( Kruglova et al, 2021 ).…”
Section: An Overview Of Organ-on-a-chip Models Applied Towards the Ge...mentioning
confidence: 99%
“…It is important to highlight that despite the fact that the pseudotyped SARS-CoV-2 virus has been widely used to study the native virus, it has several limitations worth considering, since it can only mimic the upstream cellular entry and cannot trigger the downstream immune responses within infected cells like the native virus, hence it is not suitable for studies involving immune responses ( Kruglova et al, 2021 ).…”
Section: An Overview Of Organ-on-a-chip Models Applied Towards the Ge...mentioning
confidence: 99%
“…WT and Q498A mutant were used as controls (Figure 8). A cell-cell fusion assay was used to mimic the SARS-CoV-2 virus spreading among ACE2-expressing cells (Kruglova et al, 2021;Zeng et al, 2021). This result showed that compared with the WT (RLU Ratio 4.27 ± 0.54), the V367F mutation enhanced luciferase activity (RLU Ratio 8.97 ± 0.91).…”
Section: Cell-cell Fusion Assay Analysis Of the Binding Between Mutated Spike And Ace2mentioning
confidence: 99%